Model Pengukuran Kinerja dengan Menggunakan Metode Integrated Performance Measurement Systems dan Analytical Hierarchy Process - Aisyati, Azizah; Jauhari, Wakhid Ahmad; Mulyaningtyas, Dwiningsih (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2012)
Performance measurement is important to business organization both manufacturing or service industry, and education. Performance measurement considers all activities and satisfies stakeholder’s requirements. The aim of his research is to design performance measurement in a Department in X University using Integrated Performance Measurement Systems (IPMS) method. IPMS is a performance measurement method that considers stakeholder’s requirements and measure performance integrally. IPMS method generates Key Performance Indicators (KPI) from stakeholder’s requirements by four steps, that are; identification of stakeholder’s requirements, development of external monitor, objectives establishment, and identification of KPs. Each of KPI has difference significance to performancemeasurement system. The significance of each KPI is counted by Analytical Hierarchy Process (AHP). This research results 7 performance measurement perspectives that consist of 15 objectives. The objectives can be measured by 57 KPI (consist of 43 main KPI and 24 sub KPI)